PERAN KAPABILITAS INOVASI TERHADAP PERBAIKAN PRODUK USAHA KECIL MENENGAH (UKM) DENGAN TEKANAN LINGKUNGAN DAN UKURAN PERUSAHAAN SEBAGAI VARIABEL MODERASI - Yanuarto, Eko; Rahab, Rahab; Kumorohadi, Untung (Faculty of Economics and Business Universitas Jenderal Soedirman, 2012)
This study aims to investigate the effect of innovation capability on product improvement and to test the moderating effect of environmental hostility and firm size on the relationship between innovation capability and product improvement. Respondents of this study include the businesspeople of small and medium enterprises in manufacturing sector in Purbalingga Regency, totaling 92 enterprises selected by purposive sampling. The analysis tool to test the hypotheses was Partial Least Square (PLS) using SmartPLS 2.0 software. The results show that innovation capability has a significant direct effect on product improvement, whereas environmental hostility and firm size do not moderate the relationship between innovation capability and product improvement. The results imply that the business people of small and medium enterprises should pay special attention to their firm’s capability to generate breakthroughs in order to improve product quality leading to business survival.